2008
DOI: 10.1177/016264340802300203
|View full text |Cite
|
Sign up to set email alerts
|

Using Software to Enhance the Writing Skills of Students with Special Needs

Abstract: This study used a modified multiple-baseline design to determine the effects on the writing performance of seven students with special needs when a talking word processor with spell checker software was used independent of and in conjunction with word prediction software as accommodations in daily writing exercises. Results indicated that, in general, the impact of using writing software was positive. The group mean for number of misspellings decreased, accuracy percentage increased, number of words increased,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 12 publications
3
53
2
1
Order By: Relevance
“…According to Englert et al (2007), a US National Commission on Writing in 2003 suggested that 'new technologies can advance both the teaching and learning of writing' (31). Cullen, Richards and Frank (2008) supported this idea and extended it to spelling as well as writing.…”
Section: Review Of Meta-analysis Studiesmentioning
confidence: 87%
“…According to Englert et al (2007), a US National Commission on Writing in 2003 suggested that 'new technologies can advance both the teaching and learning of writing' (31). Cullen, Richards and Frank (2008) supported this idea and extended it to spelling as well as writing.…”
Section: Review Of Meta-analysis Studiesmentioning
confidence: 87%
“…According to Englert et al (2007), a US National Commission on Writing suggested in 2003 that 'new technologies can advance both the teaching and learning of writing'. Cullen, Richards and Frank (2008) supported this idea and extended it to spelling as well as writing. However, there is currently very little research to bear out that using assistive tools should create better readers and writers.…”
Section: Introductionmentioning
confidence: 87%
“…Para ello, se utilizó un protocolo de evaluación que contenía 12 elementos (claridad y estructura del título, revisión de la literatura, rigor metodológico, citas actualizadas,…), con una escala de valoración de 0 a 5. Sin duda esta fue la etapa más laboriosa por su importancia, obteniéndose de este proceso la selección de nueve artículos (Alcaraz, Ballesta & Lozano, 2011;Atkins, Chakpitak, Sharp, Sureephong, & Wicha, 2012;Contreras & Contreras, 2011;Cullen, Richards, & Lawless, 2008;Gómez & Ortega, 2006;Hetzroni & Tannous, 2004;Tan & Mei Lin, 2012;Sánchez & Elías, 2007;Simion & Folostina, 2013) y una tesis doctoral (Ventura, 2012) (un artículo de los seleccionados constaba tanto en WOS como en SCOPUS), estudios que finalmente son parte de este meta-análisis.…”
Section: Búsqueda De La Literaturaunclassified